Forensic Linguistics in My Friend Dahmer Movie Script - Ahmad, Andi Asnufta Khairani; Maca, Sudirman; Abeng, Andi Tenri (Humaniora: Journal of Linguistics, Literature, and Education, 2025)
The research aimed at finding out the types of criminals and to describe the cause of the main character become a criminal in the movie script of My Friend Dahmer by Marc Meyers. The data were analysed through Sutherland’s theory in which the data presented in the qualitative descriptive method. The results reveal that there were four types of criminal using in the script such as white-collar crime, violent crime, property crime, and consensual crime or victimless crime. Each criminology has a different meaning from each category in each forensic linguistics. The four criminal types that the cause of the main character to become a criminal person.